A theoretical study of laser-induced ultrafast spin dynamics in trigonal monopyramidal iron and nickel complexes. Issue 40 (5th October 2022) - Liang, Xiufang; Yang, Jingying; Zhang, Yiming; Liu, Jing; Li, Chun; Lefkidis, Georgios; Hübner, Wolfgang; Jin, Wei
Abstract : A schematic illustration of the laser-induced reversible ultrafast spin crossover and the combined charge transfer and spin bifurcation achieved in complexes [R t -Bu TM] − (R = tpa/tcma, TM = Fe/Ni). Abstract : We present a first-principles study of the geometries, electronic structures, and laser-induced ultrafast spin dynamics in four trigonal monopyramidal complexes [tpa t -Bu Fe] −, [tcma t -Bu Fe] −, [tpa t -Bu Ni] −, and [tcma t -Bu Ni] − [tpa: tris-(pyrrolylmethyl)amine; tcma: tris(carbamoyl-methyl)amine; t -Bu: tert -butyl]. It is found that the low-lying level distribution of the four structures is similar, however, their spin and charge localization differs substantially. Detailed analysis demonstrates that the iron complexes have much more singly spin localized states located in the low energy region, while the nickel complexes have more charge-transfer (CT) states and more states with spin equally distributed between the Ni and the ligands. Affected by these features, more ultrafast spin-crossover (SCO) scenarios are achieved in the two iron complexes, and better CT dynamics is obtained in nickel complexes. In particular, for the CT scenarios combined with spin bifurcation, the charge is transferred from the tpa/tcma ligand to the Fe/Ni atoms, while spin-density transfer occurs in the opposite direction. Among the scenarios illustrated in the paper, the SCO processes turn out to be more complicated since they involve many more intermediate states and exhibit relatively low fidelity. In addition, the transferability of each scenario is analyzed from the absorption spectra of the initial and final states. All these results can provide significant insights into the electronic and magnetic natures of the four complexes, guide the experimental realization of the relevant scenarios, and thus promote their applications in molecular spintronics.